Sialolithotomy of the submandibular duct using sialendoscopy - Dong-Keon Lee; Euy-Hyun Kim; Chang-Woo Kim; Mong-Hun Kang; In-Seok Song; Sang-Ho Jun (SpringerOpen, 2019)
Abstract Background Conventionally, indirect radiography has been used to diagnose salivary gland diseases. However, with the development of sialendoscopy, diagnosis and treatment of salivary gland diseases have become more effective. Herein, we report a case of sialolithotomy treated with sialendoscopy and compare it with the existing methods through a literature review. Case presentation Two patients with a foreign body sensation under the tongue and dry mouth visited the Anam Hospital, Korea University. Radiographic examination revealed salivary stones inside the right Wharton duct, and the patients underwent sialolithotomy under local or general anaesthesia. The stones were totally removed, and there were no postoperative complications such as bleeding or pain. Conclusion The development of sialendoscopy has enabled better definitive diagnosis of salivary gland diseases compared with the conventional methods; better treatment outcomes can be obtained when sialendoscopy is used in appropriate cases.